Решить! 2с(с-4)^2-с^2(2с-10) при с=0,2 !

ангелочек1631 ангелочек1631    2   24.07.2019 17:10    2

Ответы
аааааа102 аааааа102  03.10.2020 11:59
2с(с-4)² - с²(2с-10) = 2с (с²-8с+16) - 2с³+10с² = 2с³-16с²+32с -2с³+10с² = 
= -6с²+32с
при с=0,2
-6*0,2 + 32*0,2 = -1,2 + 6,4 = 5,2
ПОКАЗАТЬ ОТВЕТЫ
klepekhin klepekhin  03.10.2020 11:59
2с(с-4)^2-c^2(2c-10)=2c(c^2-2c*4+4^2)-2c^3+10c^2=2c(c^2-8c+16)-2c^3+10c^2=2c^3-16c^2+32-2c^3+10c^2=6c^2+34
при с=0,2
6*0,2^2+34=6*0,4+34=36,4
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра